Obliczanie Naprężeń w Pewnym Typie Lupiny Walcowej Otwartej Poddanej Działaniu Sil Odśrodkowych - Borkowski, S. (Engineering Transactions, 1962)
This part gives a solution of the problem of discontinuity stress for a cylindrical shell of which. the form is represented by Fig. 1-7. Shells of this type are used for blades of radial pomps, compressors and blowers. The shell under consideration is composed of two cylindrical shells with different radii of curvature. The solution is reduced to the obtainment of the integration constants from the equations (6.5) and the substitution in (6.7), (6.8), (6.9). This must be done for both shells taking into consideration the fact that their dimensions are different and bearing in mind (8.2). Next, these values are inserted in (3.6) to compute the coefficients No, So, Mo and 26 of the series (3.3). In this manner are determined the integration constants C2, C4, D2 and D4, and, therefore, all the stresses [Eq. (6.3)l, which determine in a certain region including the line of contact between the shells the discontinuity stresses in the shell. For the shell of Fig. 7 the equations (10.4) and (10.5) should be taken into consideration additionally. An analysis of the numerical examples shows that in the case of the shells of Figs. 1 and 3 the maximum stresses are observed at the s 0 edge and in the case diagrams of stresses should be made for the third shell. To obtain a of the shell of Figs. 6 and 7 practically sufficient approximation it suffices to take two terms (n 1,3) of the series for the internal forces. It is observed that very short shells can be computed in a much simpler way by means of Eq. (11.5). In Tables 8-11 are collated, for the purpose of facilitating the computation, values of the coeffcients p1, q1, p2 and q2 of the constant characterizing the shell, t, in the interval 0,1-1,3.